P‐3: LTPS Device and Panel Fabrication Using Excimer Laser Dehydrogenation and Crystallization. Issue 1 (28th June 2021) - Kim, Jin Sung; Lee, Bokyoung; Kim, Aram; Yeon, Deuk Ho; Jeong, Mijin; Bang, Jungho; Nam, Seung Hee; Park, Kwon-Shik; Kim, Jeomjae; Yoon, Soo Young
Abstract : The dehydrogenation process, which is one of the important processes for manufacturing low temperature polycrystalline silicon (LTPS) devices in the industry, requires high temperature over 430–470 °C. In this paper, the hydrogen content in the a‐Si film was reduced by excimer laser annealing (ELA) at lower temperature compared with the conventional dehydrogenation process using a furnace. Not only dehydrogenation but also crystallization of a‐Si was performed in the same chamber to make poly‐Si Grain size and shape of poly‐Si seemed similar to those of poly‐Si obtained from the conventional high‐temperature furnace process. A thin film transistor (TFT) with poly‐Si channel was fabricated via this low‐temperature dehydrogenation process, and the characteristic value of the device was enough to drive the display panel. As a result, a 5.46 inch QHD panel was successfully demonstrated. It was confirmed that the optical properties of the fabricated QHD panel were at the same level as compared with control sample, which was fabricated by using the furnace process. We regard that low temperature dehydrogenation using ELA in this research is promising approach for low‐temperature process, such as transparent flexible substrates.